“Estudio de exportación de queso desde san Vicente del Caguán, Caquetá con destino a Estados Unidos” (2021)
The main reason why this project was proposed is the profitability offered by the commercialization of cheeses, since the high demand in the city allows us to identify that production can be increased and expand, not only in Colombia but in different countries, this the project consists of launching the commercialization of dairy products. Currently, Colombia is positioned among the fifteen main da iry producers in the world, which makes other countries find an opportunity to import their products. The department of Caquetá is located in the southern part of Colombia, in terms of dairy production it is among the five dairy producers in the country.